Inventarisasi Lamun (Sea Grass) di Perairan Pantai Tafamutu Kecamatan Moti Kota Ternate - Nuraini Adung Damsiki (Peneliti.net, 2022)
The objectives of this study were: 1) To take an inventory of seagrass species in Tafamutu coastal waters, 2) To determine the density, species diversity and dominance index of each seagrass species in Tafamutu coastal waters, 3) To measure temperature, salinity and visually observe the substrate. . The method used in sampling is the line transect method (Krebs, 1999) consisting of 1 station with three tracks. Density analysis using the formula according to Brauner and Zan (1977) in Krebs. (1999), the distribution pattern using the Morisita index (Krebs), the diversity of species using the Shannon-Wiener index, (1949) in Ludwiq and Reynolds (1988) and the dominance of the index using the Simpson index (Krebs, 1999). The seagrass species found in this study There are 4 species, namely Cymodocea serruluta, Cymodecea rotundata, Syringodium isoetifolium and Enhalus acoroides. From the number of species found, there were species that were not included in the quadrant, namely Halodule pinifolia and Halophila minor. The highest density was Cymodecea rotundata and the lowest was Enhalus acoroides. The highest diversity was Cymodocea serruluta and the lowest was Enhalus acoroides while the most dominant was Cymodecea rotundata. The temperature ranges from 30 – 33 °C and the salinity ranges from 33 – 35 . The substrate consists of silt mixed with sand, fine muddy sand, coarse sand mixed with coral. Suggestions that can be given in this research are the need for studies of seagrass organisms and research on nutrient content for seagrass life in Tafamutu coastal waters.